Persentase Tutupan dan Indeks Mortalitas Terumbu Karang di Perairan Pomalaa Sulawesi Tenggara - Lalang Lalang; Riska Riska; Ilham Antariksa Tasabaramo; Maharani Maharani (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
Corals are unique and specific ecosystems found in tropical waters, and are vulnerable to changes in the aquatic environment. This study aims to determine the percentage of coral reef cover and coral reef mortality index in Pomalaa waters. Coral observations were carried out at a depth of 3 m to represent shallow waters and 7 m to represent deep waters, each of which consisted of 4 observation points. The water quality parameters that were measured directly in the field were temperature, salinity, pH, water brightness and current speed using a Water Quality Checker (TOAA) and for nitrate and phosphate analysis carried out in the laboratory. The results showed that the water quality at each research station did not differ that much. The condition of coral reefs in Pomalaa waters at a depth of 3 m is categorized as damaged, with the percentage of live coral cover ranging from 11.85% - 22.07%. At a depth of 7 m the average is in moderate to damaged condition, with the percentage of cover in the range of 16.13% - 28.81%. This shows that coral diversity is generally low, so that no coral species dominates. The mortality rate of coral reefs in Pomalaa waters is high at a depth of 3 meters, namely 0.75, meaning that 75% of coral reefs are in bad condition to death, as well as at a depth of 7 meters, the highest mortality index is 0.63 meaning 63% of coral reefs in a depth of 7 meters experienced bad conditions to death.